2022
DOI: 10.1186/s12933-022-01576-8
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index in the prediction of adverse cardiovascular events in patients with premature coronary artery disease: a retrospective cohort study

Abstract: Background Premature coronary artery disease (PCAD) has become more common in recent years and is often associated with poor outcomes. Triglyceride-glucose (TyG) index is a simple and reliable surrogate for insulin resistance (IR) and is an independent predictor of cardiovascular prognosis. However, the prognostic value of the TyG index in patients with PCAD remains uncertain. Thus, this study aimed to investigate the prognostic value and predictive performance of the TyG index in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
56
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 45 publications
(63 reference statements)
11
56
3
1
Order By: Relevance
“…The metabolic syndrome is a known predictor of cardiovascular events in patients with established CAD [28][29][30]. Recent research has identified the TyG index as a reliable marker of metabolic syndrome and a strong predictor of CAD, premature CAD, and adverse events in CAD patients [10][11][12][13]28]. In our study, values of the TyG index were comparable to those from previous studies in patients with CAD, wherein TyG index values were also associated with an increased event risk [11].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The metabolic syndrome is a known predictor of cardiovascular events in patients with established CAD [28][29][30]. Recent research has identified the TyG index as a reliable marker of metabolic syndrome and a strong predictor of CAD, premature CAD, and adverse events in CAD patients [10][11][12][13]28]. In our study, values of the TyG index were comparable to those from previous studies in patients with CAD, wherein TyG index values were also associated with an increased event risk [11].…”
Section: Discussionsupporting
confidence: 82%
“…One such biomarker is the triglyceride-glucose (TyG) index, which has been proposed as a marker of metabolic syndrome and has been associated with carotid atherosclerosis, coronary artery calcification, and higher risk of cardiovascular disease [7][8][9]. Moreover, recent studies have identified the TyG index as an independent predictor of coronary calcification progression, of clinical outcomes in patients with stable CAD and premature CAD, and of cardiovascular outcomes in acute coronary syndromes [7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There were studies evidenced the improvement for predicting adverse cardiovascular events by adding the TyG index in patients after PCI and elderly ACS patients and patients with PCAD [ 24 , 38 , 39 ]. And we found that the addition of the TyG index to the baseline risk model also significantly improved its predictive value in non-diabetic general population without a history of CVD in Eastern China.…”
Section: Discussionmentioning
confidence: 99%
“…As AIP and the TyG index are associated with MACE in patients with AMI undergoing PCI [ 14 , 15 ], the effects of DAPA administration on AIP and the TyG index 12 months after discharge were evaluated. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%